Egypt's occupation : colonial economism and the crises of capitalism - Jakes, Aaron (Stanford University Press, 2020)
"This book reexamines the political economy of foreign rule and the role of political-economic thought in the struggles over the character and status of the British occupation of Egypt after 1882 through its independence in 1922. The book traces a complex history of economism, a term that refers to the reduction of social phenomena to the play of economic forces, and the intermingling of economics and politics in the colonial Egyptian context. It overturns long-standing assumptions of Egypt during the period of British occupation, and deepens our understanding of global capitalism's contradictions and the way that it defines and delimits notions of freedom, with implications that extend to the present day"--